THE USE OF TECHNOLOGY IN THE EDUCATION OF CHILDREN WITH SPECIAL NEEDS: A REVIEW OF RECENT LITERATURE - Agus Rofi'i; Arnadi Arnadi (Adisam Publisher, 2025)
The use of technology in the education of children with special needs offers great potential to improve learning quality and accessibility. Recent literature reviews have shown that technologies such as assistive devices, educational apps and online learning platforms can provide more individualised and effective solutions in supporting the academic, social and emotional development of children with special needs. However, the implementation of these technologies is not free from challenges, including cost, the need for adequate training for educators, and issues of privacy and data security. Therefore, strong collaboration between the government, educational institutions and the technology sector is needed to overcome these barriers and maximise the potential of technology in inclusive education. The study concludes that with the right approach, technology can be an important tool to meet the unique needs of children with special needs and help them reach their full potential.